2008
DOI: 10.1002/path.2343
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Alzheimer's disease amyloid precursor protein (APP) and its homologue APLP2 as essential modulators of glucose and insulin homeostasis and growth

Abstract: The amyloid precursor protein (APP), the source of the neurotoxic amyloid beta (A beta) peptide involved in Alzheimer's disease (AD), belongs to a conserved family of related proteins. In mammals, the APP family contains amyloid precursor-like protein 1 (APLP1) and amyloid precursor-like protein 2 (APLP2). Whilst a number of activities have been attributed to the APP family, an overall function has not been definitively established. While ablating either the APP or APLP2 gene in mice produces minimal phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 35 publications
(36 reference statements)
1
45
0
1
Order By: Relevance
“…Of particular interest is a recent study by Needham et al that revealed a possible new function of the APP family, namely as modulators of insulin and glucose homeostasis [118]. The study correlated the postnatal lethality in the APP -/-/APLP2 -/-knock-out mice to hyperinsulinemia and low glucose levels.…”
Section: Additional Functionsmentioning
confidence: 97%
“…Of particular interest is a recent study by Needham et al that revealed a possible new function of the APP family, namely as modulators of insulin and glucose homeostasis [118]. The study correlated the postnatal lethality in the APP -/-/APLP2 -/-knock-out mice to hyperinsulinemia and low glucose levels.…”
Section: Additional Functionsmentioning
confidence: 97%
“…Cells were harvested and analyzed by Western blot assay as described previously (21). Primary antibody concentrations were as follows: 1:2,000 for 6E10 (directed against A␤ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] ) and 1:4,000 for CT11 (directed against the C-terminal 11 amino acids of APLP1), 1:3,000 for 42464 (directed against amino acids 499 -557 of APLP1; cf. 22) and 1:5,000 for DTII (directed against full-length APLP2), 1:1,000 for CT-TACE (directed against the C-terminal 18 amino acids of TACE), and subsequently 1:5,000 for horseradish peroxidase-coupled anti-mouse IgG, anti-rabbit IgG, and protein A.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, double knock-out studies in mice demonstrated a crucial role for APLP2 in survival because APP Ϫ/Ϫ /APLP2 Ϫ/Ϫ and APLP1 Ϫ/Ϫ /APLP2 Ϫ/Ϫ mice died within the first week after birth, whereas APP Ϫ/Ϫ /APLP1 Ϫ/Ϫ mice survived (4). Recently, the mechanism for the postnatal lethality in the APP Ϫ/Ϫ / APLP2 Ϫ/Ϫ knock-out mice was correlated to hyperinsulinemia and hypoglycemia, suggesting that APP family proteins are essential modulators of glucose and insulin pathways (5). This is interesting because a relationship between diabetes mellitus and AD has been suggested, and disturbed insulin levels and signaling in AD brains have been observed (6).…”
mentioning
confidence: 99%
“…APP KO mice are viable and fertile but suffer from various defects and abnormalities, such as reduced body and brain weight, decreased size of forebrain commissures, increased frequency and severity of corpus callosum agenesis [28,30], reactive gliosis [28], increased sensitivity to kainate-induced seizures [36], increased copper and iron levels in the cerebral cortex and liver [37,38], upregulated cholesterol and sphingomyelin levels in the brain [39] and decreased plasma glucose levels as well as hyperinsulinemia [40]. Behavioral studies revealed that APP KO mice have decreased locomotor activity, reduced forelimb grip strength and deficits in the Morris water maze task as well as passive avoidance learning [41][42][43].…”
Section: App Aplp1 and Aplp2 Single Ko Micementioning
confidence: 99%